"Being responsible, respectful, trying to keep the tradition alive:" Cultural resilience and growing up in an Alaska Native community. (October 2014) - Wexler, Lisa; Joule, Linda; Garoutte, Joe; Mazziotti, Janet; Hopper, Kim
Indigenous circumpolar youth are experiencing challenges of growing up in a context much different from that of their parents and their grandparents due to rapid and imposed social change. Our study is interested in community resilience: the meaning systems, resources, and relationships that structure how youth go about overcoming difficulties. The research reflects an understanding that social and cultural ecologies influence people's available and meaningful options. The in-depth, qualitative study of 20 youth from the same Arctic community shows Inupiat (Alaska Native) youth are navigating challenges. Findings from this research suggest that Inupiat youth reflect more flexible patterns of resilience when they are culturally grounded. This cultural foundation involves kinship networks that mediate young people's access to cultural and material assets. Our participants emphasized the importance of taking care of others and "giving back to the community." Being "in the country" linked youth to traditional ontology that profoundly shifted how youth felt in relation to themselves, to others, and the world. The vast majority of participants' "fulfillment narratives" centered on doing subsistence and/or cultural activities. In relation to this, young people were more likely to demonstrate versatility in their resilience strategies when deploying coherent self-narratives that reflected novel yet culturally resonant styles. Young women were more likely to demonstrate this by reconfiguring notions of culture and gender identity in ways that helped them meet challenges in their lives. Lastly, generational differences in understandings signal particular ways that young people's historical and political positioning influences their access to cultural resources.